Strategi Guru Pendidikan Agama Islam dalam Mengimplementasikan Kurikulum 2013 - Oktapiansi, Tisna; Buyung, Wiwinda; Surahman, Surahman (JOEAI (Journal of Education and Instruction), 2023)
The purpose of this study is to describe how PAI teachers implement the 2013 curriculum in implementing learning so that students are more active in the learning process. This research is a qualitative descriptive study. This research was conducted by taking the research subjects of Islamic religious education teachers of class XI and class XII, curriculum assistants, school principals, and students of class XI and class XII at SMA Negeri 9 Bengkulu City. Data collection techniques through interviews, observation and documentation. The results of the research obtained some information such as the teacher's strategy in implementing the 2013 curriculum, learning planning, learning implementation and learning evaluation. In conclusion, the learning strategies applied by PAI teachers in implementing the 2013 Curriculum at SMA Negeri 9 Bengkulu City are discovery learning strategies, and problem based learning strategies. The implementation of the 2013 curriculum in learning Religious Education is said to have run smoothly and perfectly, in accordance with the characteristics of the 2013 curriculum, namely that it has gone according to the procedure, namely by compiling learning tools which include compiling prota, promissory notes, weekly programs, daily programs and compiling lesson plans (RPP). Keywords: PAI Teachers, Implementation of 2013 Curriculum, Learning Strategies